3. Threat: Aquaculture & agriculture - Ann Thornton; William H. Morgan; Eleanor Bladon; Rebecca K. Smith; William J. Sutherland (Coral Conservation: Global Evidence for the Effects of Actions, 2025)
This chapter highlights the threat posed to corals from marine aquaculture (mariculture) and agriculture.